Proses Pelatihan Tari Sigeh Pengunten di Sanggar RIBL SSBL Kencana Lepus Kabupaten Lampung Timur - Ralfadilla, Ananda Shalsa; Selly Oktarini; Nursilah (Jurnal Pendidikan Tari, 2025)
This study aims to describe the training process of Sigeh Pengunten Dance at Sanggar RIBL SSBL Kencana Lepus, East Lampung Regency. The research employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation conducted over one month. The results show that the training process in this studio is carried out systematically through the stages of planning, implementation, and evaluation. In the planning stage, educators determine the training objectives, materials, and methods. The implementation stage involves demonstration and direct practice methods, where students learn the dance movements under the guidance of instructors. In the evaluation stage, students' dance skills are assessed based on the elements of wiraga, wirama, and wirasa. In addition to enhancing dance skills, this training also plays a crucial role in preserving the cultural values of the East Lampung community. The findings indicate that the studio's existence is vital in maintaining the legacy of Sigeh Pengunten Dance and promoting Lampung's cultural heritage to the broader public, including tourists. This study is expected to serve as a reference for developing traditional dance training methods in Indonesia.